"Weariness" and "unpleasantness" reduce adherence to branched‐chain amino acid granules among Japanese patients with liver cirrhosis: results of a single‐center cross‐sectional survey. Issue 3 (22nd June 2016) - Eguchi, Yuichiro; Furukawa, Naoko; Furukawa, Takeshi; Egashira, Yoshimitsu; Hotokezaka, Hiroshi; Oeda, Satoshi; Iwane, Shinji; Anzai, Keizo
Abstract: Aim: Branched‐chain amino acids (BCAA) are valuable in the treatment of liver cirrhosis because they increase serum albumin levels. Poor adherence to BCAA may adversely affect prognosis, but little is known about factors predicting adherence. We undertook a survey of patients prescribed BCAA for the treatment of cirrhosis. Methods: Pharmacists carried out face‐to‐face interviews with patients (or their representatives) prescribed any of nine BCAA formulations. Question categories included patient characteristics, prescription of BCAA granules, and perceptions of BCAA administration, including adherence and possible factors that might impact adherence. "Poor adherence" was defined as "not taking the medication appropriately" or "forgetting to take the medication". Results: Overall, 253 patients (or representatives) completed the survey, of whom 135 were men, 114 were women, and 148 were ≥70 years old. Most patients (163) were prescribed BCAA for ≥2 years and were using three packs per day. Thirty‐two patients did not take their medication appropriately and 69 sometimes forgot to administer it. Weariness of taking the medication ( P  < 0.001) and the perceived unpleasantness ( P  = 0.023) of the medication in terms of its taste and volume were significantly associated with poor adherence. The patients reported that the most influential educators were general practitioners, followed by certified hepatologists, then pharmacists. Conclusion: Most patients had good adherence to BCAA in clinical practice. Poor adherence was associated with weariness with taking medication, and the unpleasantness of the medication itself. Patient education from general practitioners and hepatologists combined with adherence counseling from pharmacists may help improve adherence.